a=2b
4b=6c becomes 2b=3c
a=3c
Chat with our AI personalities
(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].
Well, honey, 2b x 2b is just 4b^2. It's like math's way of saying "I see you, I got your back." So, don't you worry about a thing, because 4b^2 is the answer to your little math problem.
18h+4b-2b
4b - 9 + 2b + 8 Coefficients are the numbers in front of the variables. Therefore the coefficient of 4b is 4 and the coefficient of 2b is 2. The like terms are 2b and 2b, but also -9 and 8. Constant terms are the ones that do not contain a variable. -9 and 8 are the constants. 4b - 9 + 2b + 8 can be simplified (by combining like terms) to give 2b - 1
4b-b